Curriculum Management: Optimizing the Education System for the Future - Hanafiah Hanafiah; Tatang Abdul Basir; Cucu Nurparid (Universitas Muhammadiyah Enrekang, 2023)
The purpose of writing this article is to comprehensively examine curriculum management using literature study methods, it is hoped that the results of this paper will dig deeply to develop scientific insights in order to achieve educational goals, especially success in the teaching and learning process as planned. The focus on writing this article includes the meaning of curriculum management, the scope of curriculum management, the function of curriculum management and the principles of curriculum management and its development. Curriculum management is the process of planning, organizing, controlling, and evaluating all curriculum components. Curriculum management is a system designed to organize and control all curriculum components, including objectives, content, teaching methods, and assessment. Helping to prepare quality school management, especially with regard to curriculum management that will be implemented at the education unit level in schools, whether it is carried out by teachers, school committees, principals, and parties related to developing curriculum at the education unit level.